Literary space axiology: Geopoetic aspect - Novikova, M.L. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
This article is the result of literary text structure research development. The special functions of the poetic language, its “separation” from all the usual communication types made it a very important object of analysis, attracting constant attention. The cross-discipline intersection of humanities, active interaction of poetics with close linguistic and humanitarian domains such as semiotics, linguistic logic analysis, cognitive science, axiology, linguistic philosophy, etc., determine the expansion of its study. The interdisciplinary research becomes especially important since it features one of the modern research characteristics - multiple paradigms that allow to analyze the object from different perspectives, in different fields of knowledge. Forming geopoetic images in a national culture is the result of different geographic regions exploration and conceptualization of these images in terms of axiology, exploring and having different experiences, materializing them in fiction through a representation of valuable meanings.